Assessing the Severity of Concerns About Preschool Children's Self-Regulation of Attention, Behavior, and Emotions Using the ABLE Universal Screener: A Rasch Analysis. (September 2020) - Barbarin, Oscar; Hitti, Aline; Brown, Jeffrey
Discerning the seriousness of socioemotional symptoms in young children can be difficult. To address this issue, the Attention, Behavior, Language, and Emotions (ABLE) universal behavioral health screener uses a rubric for severity that includes indicators of problem duration, impairment, generalizability, exacerbation, persistence, peer comparison, and need for professional intervention. This report examines whether this rubric can be treated as a unidimensional scale across respondents and problem types and streamlined for more efficient screening. Head Start teachers and parents ( N = 2, 643) reported socioemotional, attentional, behavioral, and language problems. Rasch analyses confirmed that the ABLE severity scale is unidimensional but the coherence of severity indicators differed by respondents. Consequently, greater precision in establishing clinical significance can be achieved by weighting severity items differentially for teachers and parents.